Academic experiences of shs learners studying english in distance modular approach: A phenomenological study - Espina, Arlene Lluisma; Monte, Rhea Joy Deligero (SAINTIS Publishing, 2022)
This study intended to explore and understand the academic experiences of senior high school students studying English in a distance modular approach. The researchers investigated the academic experiences, the challenges encountered, the techniques in facing challenges, and the suggestions in addressing the challenges. The four Grade 12 SHS learners of General Santos City National High School, one representing each track: Academic, TVL, Sports, and Arts and design, were the participants of this study who were selected through purposive sampling. The current qualitative inquiry is phenomenological in nature. The data were interpreted through coding, categorizing, and conceptualizing. It revealed that the academic experiences of the senior high school students are categorized into two themes; 1. Learners’ Learning Preferences and Time Management and 2. Learners’ Difficulty in Learning English. The learners experienced difficulty in understanding and comprehending lessons in English subjects. The findings also showed the learners’ learning preferences and the techniques employed in time management like the time blocking method. The challenges were the learners’ intrinsic and extrinsic motivation specifically rooted from being unmotivated and lacking parental support in tackling their learning difficulty; learners' learning preferences and time management specifically identifying their lack of time management technique; learning environment at home that shows unstable network connection and inability to allocate specific time for school work and chores; and learners' difficulty in learning English that shows the difficulty in understanding and comprehending lessons in English subjects.